Fecal microbiota transplantation for chronic constipation: a systematic review and meta-analysis of clinical efficacy, safety, and microbial dynamics - Wang, Ke; Gao, Chun; Zhu, Li; Chen, Min; Tong, Yi Xin; Zhang, Sheng (Frontiers in Microbiology, 2025)
BackgroundChronic constipation, a prevalent gastrointestinal disorder with limited treatment efficacy in refractory cases, has prompted exploration of fecal microbiota transplantation (FMT) as a novel therapeutic strategy. This systematic review and meta-analysis evaluate the efficacy, safety, and gut microbial dynamics of FMT in adults with chronic constipation.MethodsWe systematically searched PubMed, Embase, Web of Science, and Cochrane Library up to January 2025, identifying 1,072 records. Nine studies (n = 245 patients) met inclusion criteria for qualitative synthesis, with eight contributing to meta-analysis. Outcomes included constipation remission and improvement, stool metrics, quality of life, and microbiota changes. Random-effects models analyzed pooled remission rates, mean differences (MDs), and heterogeneity (I2 statistics).ResultsFecal microbiota transplantation achieved a 50.7% pooled remission rate (95% CI: 38.7%–62.7%) and 64.8% improvement rate (95% CI: 51.4%–76.3%). Significant improvements were observed in stool consistency (MD = 1.32, 95% CI: 1.05–1.35), quality of life (GIQLI MD = 32.19, 95% CI: 17.15–47.23), and symptom severity (Wexner MD = −4.83, 95% CI: −7.15–2.51). Post-FMT microbiota analyses revealed enrichment of beneficial taxa (Bifidobacterium, Prevotella; Firmicutesacteroidetes) and suppression of pro-inflammatory Enterobacteriaceae. Transient gastrointestinal adverse events (e.g., bloating: 17.3%) resolved spontaneously, with no severe complications reported.ConclusionFecal microbiota transplantation demonstrates clinically meaningful symptom relief and gut microbiota remodeling in chronic constipation, supported by favorable short-term safety. While heterogeneity in protocols and limited RCT data warrant caution, these findings advocate standardized FMT frameworks and confirmatory trials to optimize therapeutics for refractory constipation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025643634.